Development of a church education module for childless marriages - Sidabutar, Hasudungan; Binilang, Benny B.; Gerung, Farno B. A. (Edelweiss Applied Science and Technology, 2025)
The purpose of this study was to produce a module for Christian marriages that do not yet have children. This research is a development study using the Rowntree model. The product testing stage begins with validation by material experts, design experts, and language experts. After revisions, the product was tested on a number of Christian married couples who do not yet have children, specifically 3 respondents for individual trials and 25 people for field trials. The results of the study showed an average score from material experts of 4.06, indicating that the product was considered very good; from design experts, 4.46, also indicating that the product was considered very good; and from language experts, 4.45, which means that the product was considered very good. At the trial stage, the average result at the individual test stage was 4.84, indicating that the product was considered very good, and at the field trial stage, 4.41 was also considered very good. Based on interviews with pastors, very good results were obtained with an average score of 4.5. This Christian Religious Education Module in the Church for Christian couples who do not yet have children is worth using.